Thermally induced structural transformations on polymorphous silicon - Rath C.; Farjas J.; Roura P.; Kail F.; Roca i Cabarrocas P.; Bertran E. (My University, 2025)
Polymorphous Si is a nanostructured form of hydrogenated amorphous Si that contains a small fraction of Si nanocrystals or clusters. Its thermally induced transformations such as relaxation, dehydrogenation, and crystallization have been studied by calorimetry and evolved gas analysis as a complementary technique. The observed behavior has been compared to that of conventional hydrogenated amorphous Si and amorphous Si nanoparticles. In the temperature range of our experiments (650-700 °C), crystallization takes place at almost the same temperature in polymorphous and in amorphous Si. In contrast, dehydrogenation processes reflect the presence of different hydrogen states. The calorimetry and evolved gas analysis thermograms clearly show that polymorphous Si shares hydrogen states of both amorphous Si and Si nanoparticles. Finally, the total energy of the main Si-H group present in polymorphous Si has been quantified. © 2005 Materials Research Society.